Do red and blue uniforms matter in football and handball penalties? - Krenn, B.; Pernhaupt, N.; Handsteiner, M. (Journal of Sports Science & Medicine, 2017)
Past research has revealed ambiguous results on the impact of red uniforms in sports competition. The current study was aimed at analyzing the role of red and blue uniforms in football and handball penalties. Two experiments were conducted using a within subjects design, where participants rated uniform color-manipulated video clips. In the first study, participants (n = 39) watched footage of football players kicking a penalty, whereas in the second study (n = 118) videos of handball penalty takers, handball goalkeepers and football goalkeepers preparing themselves to score/save a penalty were shown. Participants rated player`s/goalkeeper`s level of confidence and the expected position of the ball crossing the goal line in the first experiment and additionally the probability of scoring the penalty against the goalkeepers in the second experiment. The videos stopped at the point where the ball was leaving the foot and hand respectively. Results did not show any beneficial impact of red uniforms. Rather, football players wearing blue were rated to kick the ball higher. The study contradicts any positive effect of red versus blue uniforms in the context of football and handball penalties, which emphasizes the need of searching for potential moderators of color`s impact on human behavior.